Co-occurrence of obesogenic behaviors and their implications for mental health during the COVID-19 pandemic: a study with university students - Bruna Carolina Rafael Barbosa; Raquel de Deus Mendonça; Elaine Leandro Machado; Adriana Lúcia Meireles (BMC, 2024)
Abstract Background The university years are a critical period for young adults, as they are more exposed to obesogenic behaviors and experience stressful situations that compromise their mental health. This study aims to estimate the prevalence of anxiety and depression symptoms and evaluate the association between the combined occurrence of obesogenic behaviors among university students. Methods A cross-sectional study was conducted on students from a public university in Brazil during the COVID-19 pandemic. Data were collected from July to August 2020 using an online questionnaire. The outcome variables (anxiety and depression symptoms) were assessed using the Depression, Anxiety and Stress Scale-21 (DASS-21). The co-occurrence of obesogenic behaviors was measured based on irregular consumption of fruits and vegetables, frequent consumption of ultra-processed foods, physical inactivity during leisure time, and sedentary behavior. A Venn diagram was used for the exploratory analysis. To verify the association between the outcome and explanatory variables, a directed acyclic graph model was constructed, and multivariate logistic regression was performed to calculate odds ratios (ORs) and 95% confidence intervals (95%CIs). Results A total of 1,353 students aged 18-24 years participated in this study. Symptoms of anxiety and depression were present in 46.1% and 54.6% of the participants, respectively. The most prevalent combination of obesogenic behaviors was frequent consumption of ultra-processed foods, physical inactivity during leisure time, and sedentary behavior (17.2%). The greater the number of simultaneous obesogenic behaviors, the higher the chance to present symptoms of anxiety [OR: 2.81 (95%CI: 1.77-4.46)] and depression [OR: 3.46 (95%CI: 2.20-5.43)]. Conclusion These findings reinforce the need to take actions to promote mental health in the university environment in conjunction with programs to promote a healthy lifestyle and improve the physical and mental well-being of students.